The concordat between the Holy See and Poland in 1925 as the source for the projects for a concordat between Chile and the Holy See in 1928 - SALINAS ARANEDA, CARLOS (Prawo Kanoniczne, 2017)
Due to the separation of the Church and the Chilean State, as stated by the Constitution of 1925, conversations took place, in order to celebrate a concordat between the Chilean State and the Holy See, without any concrete knowledge of projects aimed at this end. The opening of the Vatican Secret Archive, with reference to the funds of Pope Pius XI’s pontificate has enabled the knowledge of drafts written in 1928 by the Chilean Government with the intention of reaching an international agreement on such matter. These Chilean drafts used as a model the concordats that earlier had been agreed by the Holy See with Lithuania (1927), and Poland (1925), including various dispositions that followed closely the norms of the Polish concordat. The Chilean projects for a concordat written in 1928, and the influence on the articles exerted by the Polish concordat of 1925 are herein presented and analyzed.